Budaya Inklusif dalam Komunikasi Pendidikan Anak (Stud Etnografi Komunikasi pada Sekolah Dasar Inklusif di Bandung) - Ike Junita Triwardhani (MediaTor (Jurnal Komunikasi), 2020)
Inclusive education is education for all; it is a form of resistance to discriminatory treatment in education through the provision of effective education for all children. In inclusive schools, children with normal conditions will learn together with special needs children. Normal students in inclusive schools will learn to build sensitivity and develop their social intelligence, while students with special needs learn to build confidence and develop more of their abilities. This paper aims to analyze and map the cultural development in the implementation of inclusive education for children. The case chosen is an inclusive school in Bandung which implements inclusive education. This paper uses ethnographic of communication method by tracking communication patterns established from the interactions of actors in a community group, namely communication between normal students and special needs students in inclusive schools. Field data explain that the interaction process results in an inclusive culture that develops in schools. The results show that inclusive cultures built are giving opportunities and trust, helping spontaneously, reminding each other, respecting personalities, building discipline, developing tolerance, and carrying out all activities based on religious precepts. The culture built in an inclusive school produces harmony in the implementation of learning by accommodating the diverse needs of students.